Spin-orbital effects in metal-dichalcogenide semiconducting monolayers - Reyes-Retana, J. A. (Nature Publishing Group, 2016)
Metal-dioxide & metal-dichalcogenide monolayers are studied by means of Density Functional Theory. For an accurate reproduction of the electronic structure of transition metal systems, the spin orbit interaction is considered by using fully relativistic pseudopotentials (FRUP). The electronic and spin properties of MX2 (M = Sc, Cr, Mn, Ni, Mo & W and X = O, S, Se & Te) were obtained with FRUP, compared with the scalar relativistic pseudopotentials (SRUP) and with the available experimental results. Among the differences between FRUP and SRUP calculations are giant splittings of the valence band, substantial band gap reductions and semiconductor to metal or non-magnetic to magnetic “transitions”. MoO2, MoS2, MoSe2, MoTe2, WO2, WS2 and WSe2 are proposed as candidates for spintronics, while CrTe2, with μ ~ 1.59 μB, is a magnetic metal to be experimentally explored.